PERILAKU DAN LAJU SERANGAN PENGGEREK KAYU DI LAUT PADA KAYU TUSAM (PINUS MERKUSII JUNGH. et de Vr.) - Mohammad Muslich (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This study is intended to recognize the behaviour and infestation rate of marine borers. Forty samples of pine wood, measuring 120 cm x 5 cm x 5 cm,. vertically floated at Ram but Island seashore. These samples are divided in to three section: top, midle and bottom. The observation were carried out after 1, 2, 3 and 6 months by splitting the sample.The results showed that the infestation started from the bottom upwards. The length and diameter of the burrow is controlled to a certain extent by the intensity of the borer population in the wood. When crowded, the borer may grow only a few cm. After six months of experiment, the infestation rate of samples showed the following regression equation; i.e, top section Y 1= 0, 134 (X)2,375, milde section Y2= 2,569 (X)1,113 and bottom section Y 3= 3,334 (X)0,142.